Daur Ulang Oli Bekas Menjadi Bahan Bakar Diesel dengan Proses Pemurnian Menggunakan Media Asam Sulfat dan Natrium Hidroksida - I Nyoman Suparta; Ainul Ghurri; Wayan Natha Septiadi (Jurnal Mettek: Jurnal Ilmiah Nasional dalam Bidang Ilmu Teknik Mesin, 2015)
Consumption of processed oil to always increase every year in line with the increase in population and activity of the world's population. Alternative energy also intensively carried out in order to save fuel consumption mainly on transport and existing conventional machines. Various attempts and studies have been done to save diesel fuel in diesel engines, among others, by using bio-diesel derived from plants. Besides the need for fuel increases with the progress of the construction industry and the rest from industrial processes and machinery that can not be handled properly is waste that number continues to rise, among other things used oil. Therefore, the oil is taken from petroleum, the hydrocarbon is a compound that has an energy value and flammable, it is necessary to look for ways to utilize primarily used oil fuel.Therefore it is necessary to find a way to utilize the used oil as a fuel in a diesel engine with an easy and inexpensive process.